The Effect Of Giving Social Rewards And Recognition On The Independence Of Children Aged 4-5 At Tk Adhyaksa 23 Mataram - Mulyan, Andi; Musda, Andi (JUPE : Jurnal Pendidikan Mandala, 2025)
The purpose of this study is to get reliable information regarding the impact of social rewards and attitudes on the well-being of children aged four to five years old who are enrolled in the TK Adhyaksa 23 Mataram. "Kemandirian anak usia dini" refers to the ability of the child to carry out daily activities and tasks in a completely independent manner or with a small amount of assistance, depending on the circumstances of the child's development. This research makes use of the quantitative approach in conjunction with the experimental methodology. Twenty children between the ages of four and five years old were the subjects of the study. In order to collect data, an observation was carried out using an instrument for determining the age of the child, which has previously been evaluated for its validity and reliability. The analysis of the data is performed using the independent sample t-test (uji t). According to the findings of the research, there are significant benefits that may be derived from the exchange of social rewards and the acquisition of knowledge on the well-being of children of both genders. The value of t is 0.777, and the significance level (two-tailed) is 0.443, which is less than 0.05. This indicates that the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted. According to this, the pemberian reward social and the pengakuan terbukti have the ability to increase the kemandirian of kids between the ages of four and five. It is hoped that the findings of this research will serve as a guide for teachers and other individuals in the process of formulating educational strategies that address the needs of children as soon as they are born.